Ethanol gas sensor based upon ZnO nanoparticles prepared by different techniques - Sonik Bhatia; Neha Verma; R.K. Bedi (Results in Physics, 2017)
Nowadays, applications of nanosized materials have been an important issue in basic and applied sciences. In this investigation, Zinc Oxide (ZnO) nanoparticles were prepared by two different techniques (simple heat treatment, thermal evaporation-two zone furnaces). In order to control shape and size – ZnO nanoparticles prepared from heat treatment were used as a source for thermal evaporation method by using two zone split furnace by varying zone temperature (Zone 1–800 °C and Zone 2–400 °C). For both techniques 0.17 M of Zn acetate dihydrate is used as main precursor and film is deposited on glass substrate. Synthesized ZnO were characterized for XRD, FESEM, FTIR and UV–Vis spectrophotometer and LCR meter. XRD revealed hexagonal wurtzite structure with preferential orientation along (1 0 1) plane. FESEM observed that grain size in the range of range of ∼50 ± 5 nm. FTIR spectra showed that the peaks between 400 and 500 cm−1 for ZnO stretching modes. Optical properties has been studied and found that the observed band gap lies in the range of 3.32–3.36 eV. The higher value of capacitance is observed at lower frequency. Gas sensing properties showed the higher response in case of thermal evaporation as compared to simple heat treatment at an operating temperature of 250 °C. Keywords: ZnO nanoparticles, Simple heat treatment, Thermal evaporation, Gas sensor